Further properties of the fuzzy complete a-fuzzy normed algebra - Abbas, Rasha Khudhur; Kider, Jehad R. (Iraqi Journal of Science, 2024)
In this paper further properties of the fuzzy complete a-fuzzy normed algebra have been introduced. Then we found the relation between the maximal ideals of fuzzy complete a-fuzzy normed algebra and the associated multiplicative linear function space. In this direction we proved that if is character on Z then ker is a maximal ideal in Z. After this we introduce the notion structure of the a-fuzzy normed algebra then we prove that the structure, st(Z) is -fuzzy closed subset of fb(Z, ) when (Z, , , ) is a commutative fuzzy complete a-fuzzy normed algebra with identity e.